2010
DOI: 10.1016/j.visres.2010.05.009
|View full text |Cite
|
Sign up to set email alerts
|

On the launch-site effect for skipped words during reading

Abstract: The launch-site effect, a systematic variation of within-word landing position as a function of launch-site distance, is among the most important oculomotor phenomena in reading. Here we show that the launch-site effect is strongly modulated in word skipping, a finding which is inconsistent with the view that the launch-site effect is caused by a saccadic-range error. We observe that distributions of landing positions in skipping saccades show an increased leftward shift compared to non-skipping saccades at eq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
28
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(33 citation statements)
references
References 25 publications
4
28
1
Order By: Relevance
“…Landing-position distributions are decomposed into cases after skipping saccades (black) and onestep saccades (grey) (from . With respect to the random variability of saccadic landing positions (Figure 2b), Krügel and Engbert (2010) observed that landing positions in skipping saccades are associated with a generally greater variability, confirmed by consistently larger standard deviations of the fitted normal distributions. Moreover, the standard deviations of the distributions of landing positions in word-skipping saccades markedly increased with increasing launch-site distances, whereas the standard deviations of the landing distributions in one-step saccades only slightly increased with longer target-word distances.…”
Section: Word Skippingmentioning
confidence: 55%
See 3 more Smart Citations
“…Landing-position distributions are decomposed into cases after skipping saccades (black) and onestep saccades (grey) (from . With respect to the random variability of saccadic landing positions (Figure 2b), Krügel and Engbert (2010) observed that landing positions in skipping saccades are associated with a generally greater variability, confirmed by consistently larger standard deviations of the fitted normal distributions. Moreover, the standard deviations of the distributions of landing positions in word-skipping saccades markedly increased with increasing launch-site distances, whereas the standard deviations of the landing distributions in one-step saccades only slightly increased with longer target-word distances.…”
Section: Word Skippingmentioning
confidence: 55%
“…Interestingly, within-word landing positions 336 KRÜGEL AND ENGBERT after skipping saccades differ from landing positions after one-step saccadeseven if they are launched from the same distances to the target words. Krügel and Engbert (2010); demonstrated that word skipping strongly modulates where the eyes land within the target word (see also Drieghe, Pollatsek, Staub, & Rayner, 2008;Krügel, Vitu, & Engbert, 2012;Radach, 1996;Radach & McConkie, 1998). Figure 1 presents experimental data for the distributions of landing positions within words of different length for skipping saccades and one-step saccades, both launched from equal distances.…”
Section: Word Skippingmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, they argued that fixation locations are subject to a saccadic range error that results in deviations from the intended fixation locations. Finally, Krügel and Engbert (2010) discovered that the launch-site effect is strongly modulated by word skipping. If the word before the target is skipped, the distribution of fixation locations is shifted leftwards compared to nonskipping saccades.…”
Section: Introductionmentioning
confidence: 99%